3D printing of human ear pinna using cartilage specific ink. (3rd August 2021) - Bhamare, Nilesh; Tardalkar, Kishor; Parulekar, Pratima; Khadilkar, Archana; Joshi, Meghnad
Abstract: Biofabrication of a complex structure such as ear pinna is not precise with currently available techniques. Auricular deformities (e.g. microtia) can cause physical, social as well as psychological impacts on a patient's wellbeing. Currently available surgical techniques and transplantation methods have many limitations that can be overcome with the help of 3D bioprinting technology. Printable bioink enriched with cartilage-specific extracellular matrix (ECM) synthesis was done by digesting goat ear pinna cartilage and polymerized by adding polyvinyl alcohol and gelatine. Rheological analysis and Fourier-transform infrared spectroscopy were used for the characterization of bioink to get desired viscosity and polymerization. Human ear pinna was printed using extrusion method and computer-aided design, stereolithography software which facilitated the automated printing in relatively less time without continuous monitoring. Thermal degradation of pinna was checked by thermal gravimetric analysis. Biodegradability and swelling of ear pinna were observed for understanding the nature of pinna and the impact of external factors. Reconstructed pinna's biocompatibility was proved by in ovo and in vivo studies. The occurrence of angiogenesis in the grafted ear manifested the capacity of proliferation and engraftment of cartilage cells. Histology and SEM analysis revealed the recellularization and the synthesis of ECM components such as glycosaminoglycan and collagen in transplanted 3D printed ear pinna. The expression of CD90+ which indicated newly synthesized cartilage in the transplanted 3D printed ear pinna. The absence expression of CD14+ also indicated acceptance of xenogenic transplanted 3D printed ear pinna. Transplantation of 3D ear pinna was successful in an animal model and can be utilized as tissue engineered ear bank.